Breast cancer diagnosis based on lipid profiling by probe electrospray ionization mass spectrometry. Issue 6 (4th April 2020) - Iwano, T; Yoshimura, K; Inoue, S; Odate, T; Ogata, K; Funatsu, S; Tanihata, H; Kondo, T; Ichikawa, D; Takeda, S
Graphical Abstract: Probe electrospray ionization mass spectrometry (PESI-MS) is an ambient ionization-based mass spectrometry method that surpasses the original electrospray ionization technique in features such as the rapidity of analysis, simplicity of the equipment and procedure, and lower cost. This study found that the PESI-MS system with machine learning has the potential to establish a lipid-based diagnosis of breast cancer with higher accuracy, using a simpler approach. Rapid mass spectrometry for breast cancer